FOREWORD - Christian BYK (Journal international de bioéthique et d'éthique des sciences, 2023)
The questions, even if they are burning, that current events pose to us, no more than the passions that arouse situations felt to be unjust, cannot totally guide our analysis and our interrogations on how to act to remedy them. At the time when we invited our Russian colleagues to elaborate this issue, Russia’s second war against Ukraine had not yet been engaged with its extreme humanitarian consequences – or rather “inhumanity” – for the invaded country, martyred in its population as well as in its national identity. The consequences, still difficult to measure, of this invasion wanted by the Russian power as a major political project aiming at putting the country back in its “historical trajectory”, are now measured at the international level in political, economic and cultural dimensions, including sanctions against Russia. Should the immediate time then disrupt a work which, because it is academic, would be at odds with the present situation? Should we postpone the publication of academic works, which are part of a longer time frame, that B. Lichertman, the guest editor of this issue, places in the continuity of a previous issue published in 2005. We have chosen to think, on the contrary, that these texts, diverse as to what they say and how they say it, are a testimony, through the prism of questions concerning medical ethics, of what Russia is today and that they thus bring a useful glance to better analyze Russian society. It is true that the philosophy of bioethics, which I share, is to consider it as a phenomenon revealing the social transformations of a society. This is what I said in 1994 to Yvan Frolov, the first president of the National Bioethics Commission of Russia and the promoter of Perestroika with Gorbachev. And now, let the reader be the judge!